ab+a+b+6+3ab-b+c-6=

Simple and best practice solution for ab+a+b+6+3ab-b+c-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ab+a+b+6+3ab-b+c-6= equation:


Simplifying
ab + a + b + 6 + 3ab + -1b + c + -6 = 0

Reorder the terms:
6 + -6 + a + ab + 3ab + b + -1b + c = 0

Combine like terms: 6 + -6 = 0
0 + a + ab + 3ab + b + -1b + c = 0
a + ab + 3ab + b + -1b + c = 0

Combine like terms: ab + 3ab = 4ab
a + 4ab + b + -1b + c = 0

Combine like terms: b + -1b = 0
a + 4ab + 0 + c = 0
a + 4ab + c = 0

Solving
a + 4ab + c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1c' to each side of the equation.
a + 4ab + c + -1c = 0 + -1c

Combine like terms: c + -1c = 0
a + 4ab + 0 = 0 + -1c
a + 4ab = 0 + -1c
Remove the zero:
a + 4ab = -1c

Combine like terms: -1c + c = 0
a + 4ab + c = 0

The solution to this equation could not be determined.

See similar equations:

| 6(2x-7)=33 | | x^5+5ifx=-2 | | 32x^2+32x-1=0 | | 9q-(7q+12)=6-(2q-7) | | (3a+2)(3a-1)=0 | | 3a+2=3a-6 | | -5+(-15d+1)=2(7d-17)-d | | .07x+.03y=366 | | 5m+6km-8hm=m | | 15-4x=45+10x | | 8s^2-9s+2=0 | | d^2-18d+81=13 | | 5m+6km-8hm= | | =i^103 | | 4s^2-8=0 | | .66y=12 | | 24=-.33t | | .20n=-9 | | 4s^2-3s=0 | | 3(x^2-14x+49)=-14 | | 9s^2+2s-9=0 | | 3s^2-9s-6=0 | | 6(1+2x)-(8x-7)=17 | | w-11=3 | | 2(x)-8=x-7 | | 5v+25= | | 5(15x+5)=415 | | cos(x)=11x | | 7x^2+5x+h=0 | | ln(x+35)-ln(x-1)=ln(x-5) | | 6s^2+5s=0 | | 2+10(4x+5)= |

Equations solver categories